Targeted lipid nanoparticle delivery of calcitriol to human monocyte-derived macrophages in vitro and in vivo: investigation of the anti-inflammatory effects of calcitriol - Rafique A; Etzerodt A; Graversen JH; Moestrup SK; Dagnæs-Hansen F; Møller HJ (International Journal of Nanomedicine, 2019)
Aisha Rafique,1 Anders Etzerodt,2 Jonas H Graversen,3 Søren K Moestrup,3 Frederik Dagnæs-Hansen,2 Holger Jon Møller1 1Department of Clinical Biochemistry, Aarhus University Hospital, Aarhus, Denmark; 2Institute of Biomedicine, Aarhus University, Aarhus, Denmark; 3Department of Molecular Medicine, University of Southern Denmark, Odense, Denmark Background: Vitamin D3 possesses anti-inflammatory and modulatory properties in addition to its role in calcium and phosphate homeostasis. Upon activation, macrophages (M) can initiate and sustain pro-inflammatory cytokine production in inflammatory disorders and play a pathogenic role in certain cancers. Purpose: The main purpose of this study was to encapsulate and specifically target calcitriol to macrophages and investigate the anti-inflammatory properties of calcitriol in vitro and in vivo.Methods: In this study we have designed and developed near-infrared calcitriol PEGylated nanoparticles (PEG-LNP(Cal)) using a microfluidic mixing technique and modified lipid nanoparticles (LNPs) to target the M specific endocytic receptor CD163. We have investigated LNP cellular uptake and anti-inflammatory effect in LPS-induced M in vitro by flow cytometry, confocal microscopy and gene expression analyses. LNP pharmacodynamics, bio-distribution and organ specific LNP accumulation was also investigated in mice in vivo. Results: In vitro, we observed the specific uptake of PEG-LNP(Cal)-hCD163 in human M, which was significantly higher than the non-specific uptake of control PEG-LNP(Cal)-IgG(h) in M. Pre-treatment with encapsulated calcitriol was able to attenuate intracellular TNF- expression, and M surface marker HLA-DR expression more efficiently than free calcitriol in LPS-induced M in vitro. Encapsulated calcitriol diminished mRNA gene levels of TNF-, NF-B, MCP-1 and IL-6, while upregulating IL-10. TNF- and IL-6 protein secretion also decreased. In mice, an in vivo pharmacodynamic study of PEG-LNP(Cal) showed a rapid clearance of IgG and CD163 modified LNPs compared to PEG-LNP(Cal). Antibody modified PEG-LNP(Cal) accumulated in the liver, spleen and kidney, whereas unmodified PEG-LNP(Cal) accumulation was only observed in the liver.Conclusion: Our results show that calcitriol can be effectively targeted to M. Our data confirms the anti-inflammatory properties of calcitriol and this may be a potential way to deliver high dose bioactive calcitriol to M during inflammation in vivo. Keywords: macrophages, 1.25(OH)2D3, calcitriol, lipid nanoparticles, pro-inflammatory cytokines, CD163 targeted drug delivery, gene expression analyses, in vivo pharmacodynamics